Intrapleural Bortezomib for the Therapy of Myelomatous Pleural Effusion: A Case Report - Magdalena Klanova; Pavel Klener; Marek Trneny; Jan Straub; Ivan Spicka (Case Reports in Immunology)
Myelomatous pleural effusion (MPE) is an extremely rare manifestation of multiple myeloma (MM). We present a case of MPE in a patient with IgG-κ MM treated with intrapleural bortezomib with systemic bortezomib-based therapy. Although we observed good local response, the patient succumbed due to systemic myeloma progression.